2017
DOI: 10.1016/j.acvd.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

COLIN trial: Value of colchicine in the treatment of patients with acute myocardial infarction and inflammatory response

Abstract: In our study, the effect of colchicine on inflammation in the context of STEMI could not be demonstrated. Further larger studies may clarify the impact of colchicine in acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 19 publications
4
106
1
4
Order By: Relevance
“…A smaller study of 44 patients, however, with a followup of 1 month, randomized patients with STEMI to colchicine 1 mg/d plus OMT or OMT alone and found no difference in mean peak CRP value during the index hospitalization between the 2 groups (Table). 51 In a prospective, observational study of 80 patients with ACS allocated in a 1:1 ratio to OMT alone or OMT with colchicine 0.5 mg/d for 12 months, computed tomography coronary angiography was performed at baseline and 12 months (Table). 8 OMT involved risk factor optimization and statin intensification therapy aiming at an LDL-C level <1.8 mmol/L.…”
Section: The Role Of Colchicinementioning
confidence: 99%
“…A smaller study of 44 patients, however, with a followup of 1 month, randomized patients with STEMI to colchicine 1 mg/d plus OMT or OMT alone and found no difference in mean peak CRP value during the index hospitalization between the 2 groups (Table). 51 In a prospective, observational study of 80 patients with ACS allocated in a 1:1 ratio to OMT alone or OMT with colchicine 0.5 mg/d for 12 months, computed tomography coronary angiography was performed at baseline and 12 months (Table). 8 OMT involved risk factor optimization and statin intensification therapy aiming at an LDL-C level <1.8 mmol/L.…”
Section: The Role Of Colchicinementioning
confidence: 99%
“…In the present review, there was an inconsistent effect with respect to lowering of CRP among patients randomized to colchicine therapy 11,12 . Furthermore, two additional studies found no significant difference in CRP levels with colchicine in patients with an acute coronary syndrome 25,26 …”
Section: Discussionmentioning
confidence: 60%
“…23 This form of HF is characterized by the correlation between adverse clinical events and raised serum/myocardial concentrations of pro-inflammatory cytokines. 24,25 With respect to the pathological mechanism, inflammation has been documented as a critical event in AMI-induced HF. 4,25 Following myocardial infarction, the primary objective of the inflammatory response in the heart is to repair tissue injury, thereby allowing the heart to adapt to the bad conditions in the short-term and ultimately return to homeostasis and recover cardiovascular function in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of all HF patients suffer from declined ejection fraction (typically considered as EF <40%) 23 . This form of HF is characterized by the correlation between adverse clinical events and raised serum/myocardial concentrations of pro‐inflammatory cytokines 24,25 . With respect to the pathological mechanism, inflammation has been documented as a critical event in AMI‐induced HF 4,25 .…”
Section: Discussionmentioning
confidence: 99%